Your faith and you : a synthesis of Catholic belief - Finley, James; Pennock, Michael (Notre Dame, Indiana : Ave Maria Press, 1978)
Presents the basic beliefs of contemporary Catholicism as reflected in Vatican II statements and modern scriptural studies.
Keywords: Catholic Church -- Doctrines; Catholic Church -- Doctrines; Theology, Doctrinal -- Popular works